Embryo rescue as a method to develop and multiply a backcross population of cassava (Manihot esculenta Crantz) from an interspecific cross of Manihot esculenta ssp. Flabellifolia - Akinbo, Olalekan; Labuschangne, M.; Fregene, Martin A. (Academic Journals, 2010)
Cassava is one of the most planted tuber crops in the tropical world. The importance of cassava is growing as a food security crop in sub Saharan Africa, where malnutrition is a menace. However, a major hindrance in the fast improvement of the crop is the long generational cycle of cassava and poor germination of the seeds, and the low multiplication rate of the stem cuttings. In vitro germination of 495 seeds from backcross population was done. Each genotype was multiplied for sufficient planting material, hardened in the green house and transplanted to the field. Percentage germination of the seeds in embryo culture was high (66%). Raising plantlets in the green house was found to be useful to select healthy plants and thus obtain a uniform stand in the field. The genotypes were planted in a single row trial and harvested eight months after planting. Transplanted plantlets gave 98.89% establishment. Yield-related traits were significantly high compare to the result from the past experiments. The high percentage of plant recovery from seed through to the field is a means of overcoming some problems associated with the traditional method of cassava breeding through direct seed planting to generate planting materials.